L2 Perception and Production of Japanese Lexical Pitch: A Suprasegmental Similarity Account - Laméris, Tim Joris; Graham, Calbert (Journal of Monolingual and Bilingual Speech, 2020)
Adults are known to have difficulties acquiring suprasegmental speech that involves pitch (f0) in a second language (L2) (Graham & Post, 2018; Hirata, 2015; Wang, Spence, Jongman & Sereno, 1999; Wong & Perrachione, 2007). Previous research has suggested that the perceived similarity between L1 and L2 phonology may influence how easily segmental speech is acquired, but this notion of ‘similarity’ may also apply to suprasegmental speech (So & Best, 2010; Wu, Munro & Wang, 2014). In this paper, the L2 acquisition of Japanese lexical pitch was assessed under a ‘Suprasegmental Similarity Account’, which is a theoretical framework inspired by previous models of segmental and suprasegmental speech (Best & Tyler, 2007; Flege, 1995; Mennen, 2015) to account for the L2 acquisition of word prosody. Eight adult native speakers of Japanese and eight adult English-native advanced learners of Japanese participated in a perception and production study of Japanese lexical pitch patterns. Both groups performed similarly in perception, but non-native speakers performed significantly worse in production, particularly for ‘unaccented’ Low–High–High patterns. These findings are discussed in light of the ‘Suprasegmental Similarity Account’.